The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00383771
|View full text |Cite
|
Sign up to set email alerts
|

Mesodermal induction in early amphibian embryos by activin A (erythroid differentiation factor)

Abstract: Recently the mesoderm-inducing effects of the transforming growth factor β (TGF-β) family of proteins have been widely examined. In an attemt to elucidate the functions of these proteins, porcine inhibin A and activin A (erythroid differentiation factor; EDF) were examined. Treatment of explants with activin A led to differentiation of mesodermal derivatives such as mesenchyme, notochord, blood cells and muscle, but inhibin A had a much lesser effect. The mesodermal differentiation induced by activin A was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(117 citation statements)
references
References 22 publications
0
117
0
Order By: Relevance
“…As mesoderm is induced by the activin/nodal signaling pathway (Asashima et al, 1990;Smith et al, 1990;Tiedemann et al, 1992;Agius et al, 2000), we further tested if TM treatment had any influence on the activity of activin A in mesoderm induction using animal cap assays. Embryos were treated with 2 g/ml TM from 2-cell stage till stage 8.5.…”
Section: Tm Treatment Has No Effect On Activin a Induced Mesoderm Formentioning
confidence: 99%
“…As mesoderm is induced by the activin/nodal signaling pathway (Asashima et al, 1990;Smith et al, 1990;Tiedemann et al, 1992;Agius et al, 2000), we further tested if TM treatment had any influence on the activity of activin A in mesoderm induction using animal cap assays. Embryos were treated with 2 g/ml TM from 2-cell stage till stage 8.5.…”
Section: Tm Treatment Has No Effect On Activin a Induced Mesoderm Formentioning
confidence: 99%
“…In vivo, the importance of the nodal subfamily in gene regulation in early development is well established (Schier and Shen, 2000;Whitman, 2001), but a role for activin remains uncertain. Originally recognized as a mesoderm inducer (Smith et al, 1990;Asashima et al, 1990), activin played a large part in the study of early development in subsequent years. Although activin-like protein has been reported to be present in the early Xenopus embryo (Asashima et al, 1991), direct evidence for its involvement in embryogenesis has been difficult to obtain.…”
Section: Nodal Signaling Is Required For Zebrafish Lim1 Gene Activationmentioning
confidence: 99%
“…An effective system for the study of transcriptional regulation of Xlim-1 is provided by Xenopus animal explants, which respond to inducing factors such as activin by activation of mesodermal genes including Xlim-1 (Smith, 1987;Smith et al, 1990;Asashima et al, 1990;Taira et al, 1992;reviewed in Dawid, 1994). This system allows us to isolate the activin/nodal response of the Xlim-1 gene from other regulatory inputs, which seemed desirable as this gene is expressed at later stages in complex patterns, presumably necessitating a variety of regulatory inputs (Taira et al, 1992(Taira et al, , 1994aKaravanov et al, 1996;Hayes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have identified activin and homologues thereof as factors that induce all mesodermal tissue types in the animal cap assay (Asashima et al, 1989(Asashima et al, , 1990aSmith et al, 1990;Sokol et al, 1990;van den Eijnden-Van Raaij et al, 1990). Activin, which is one of the transforming growth factor ␤ (TGF-␤) family proteins, stimulates the activin/Nodal signal pathway, one of the key signaling pathways in embryonic development.…”
Section: Introductionmentioning
confidence: 99%